Perceptions of Pafos as European Capital of Culture: tourism stakeholder and resident perspectives - Farmaki, Anna; Christou, Prokopis A.; Saveriades, Alexis; Spanou-Tripinioti, Elena (My University, 2019)
The purpose of this paper is to qualitatively examine the perceptions of the residents of Pafos regarding the European Capital of Culture (ECoC) title awarded to the city in 2017, in response to the need for greater research on residents' perceptions within the context of cultural events. Utilizing the social exchange theory, the study identifies four types of residents based on their “perceptions” and “involvement in the tourism industry” and concludes that resident support of the ECoC initiative is impaired by the governance structure in place in the awarded city as well as factors emanating from the socio-political environment.
Keywords: Cultural events; Cyprus; European Capital of Culture; Residents' perceptions; Social exchange theory